The financial impact of direct and indirect taxes on a company in Business Rescue - Rebello, Dustin Wade (Department of Finance and Tax, 2017)
Companies form the backbone of the South African economy and contribute significantly to the tax revenue of the country through both direct and indirect taxes. As a result of the 2007/2008 financial crisis businesses, especially private companies, have been under increasing financial pressure with many companies finally being liquidated as a result of these financial pressures. In 2011, as a means to aid financially distressed companies, the government introduced the concept of Business Rescue ("BR") into law through Chapter 6 of the Companies Act, No 71. of 2008 ("Companies Act"). Despite this attempt by government to provide companies with a means of financial relief BR has been relatively unsuccessful in SA with very few companies managing to be rescued. Companies due to their very nature are subject to many laws and regulations. It is for this reason that, when trying to consider the effectiveness of a particular law or regulation, one must look not only at the primary law but also consider the impact of any auxiliary laws and regulations that work in conjunction with the primary law. This dissertation therefore seeks to understand the financial impact of direct and indirect taxes ("Tax Laws") on a company in BR in order to determine whether these laws support or hinder BR. In this dissertation an overall understanding of BR is obtained by considering the development of BR in SA, the BR process as detailed in the Companies Act and the application of BR in SA including various statistics relating to BR. Thereafter we obtain an overall understanding of the Tax Laws that have been introduced in to SA law since the introduction of BR in SA law as well as some existing provisions of the Tax Laws that are applicable to companies in BR. From the understanding of these two laws we develop a financial evaluation criterion that is used to assess the financial impact of various tax strategies on a company in BR. For the final assessment of the financial impact of the Tax Laws an assessment is performed on the deductibility of BR expenditure in terms of S11(a) and 23(g) of the Income Tax Act, No. 58 of 1962 ("ITA"). Ultimately a conclusion is reached on the financial impact that the Tax Laws have on a company in BR and, at a high level, additional considerations that may improve the success rate of rehabilitating companies in BR.